Effects of intra‐articular hyaluronic acid injection on immunohistochemical characterization of joint afferents in a rat model of knee osteoarthritis. (18th March 2015) - Ikeuchi, M.; Izumi, M.; Aso, K.; Sugimura, N.; Kato, T.; Tani, T.
Abstract: Background: Intra‐articular hyaluronic acid (HA) injection, known as viscosupplementation, is a widely used therapy for pain relief in knee osteoarthritis (OA). Long‐term clinical efficacy of HA has been reported in spite of a relatively short residence time. Herein, we evaluated our hypothesis that intra‐articular HA injection could reduce the OA‐associated changes in joint afferents. Methods: OA was induced by intra‐articular injection of mono‐iodoacetate in rats. Animals in the OA + HA group were given three weekly intra‐articular HA injections. Pain‐related behaviours, including weight‐bearing asymmetry and mechanical hyperalgesia of the paw, knee joint histology and immunohistochemistry of joint afferents identified by retrograde labelling, were compared between groups (naïve, OA and OA + HA). Results: OA rats showed pain‐related behaviours and up‐regulation of pain‐related neurochemical markers [calcitonin gene‐related peptide (CGRP), tyrosine receptor kinase A (TrkA) and acid‐sensing ion channel 3 (ASIC3)] in joint afferents. HA injections reduced not only the severity of OA and pain behaviours but also OA‐associated neurochemical changes in joint afferents. The differences between OA and OA + HA were statistically significant in CGRP (61 ± 10% vs. 51 ± 10%; p  = 0.0406) but not significant in TrkA (62 ± 10% vs. 54 ± 9%; p  = 0.0878) and ASIC3 (38 ± 9% vs. 32 ± 8%; p  = 0.3681). Conclusion: Intra‐articular HA injections reduced the severity of OA, decreased mechanical hyperalgesia of the paw, but not weight‐bearing asymmetry, and attenuated OA‐associated up‐regulation of CGRP, but not TrkA and ASIC3, in joint afferents. The modulatory effects of HA on joint afferents is one of the underlying mechanisms of the gap between HA residence time and duration of clinical efficacy.